2017
DOI: 10.1063/1.4978271
|View full text |Cite
|
Sign up to set email alerts
|

Radial tunnel diodes based on InP/InGaAs core-shell nanowires

Abstract: We report on the fabrication and characterization of radial tunnel diodes based on InP(n+)/InGaAs(p+) core-shell nanowires, where the effect of Zn-dopant precursor flow on the electrical properties of the devices is evaluated. Selective and local etching of the InGaAs shell is employed to access the nanowire core in the contact process. Devices with an n+-p doping profile show normal diode rectification, whereas n+-p+ junctions exhibit typical tunnel diode characteristics with peak-to-valley current ratios up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Recently, an Esaki diode between materials with interest for tandem within a NW (GaInP/InP) has been demonstrated (see Figure c,d), but in the same article, the authors illustrate the difficulties associated with the doping value and profile of cathode and anode by trying different dopants and growth directions (p–n or n–p). Core–shell radial Esaki tunnel diodes have been reported as well. , …”
Section: Iii–v Nanowire Growth and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an Esaki diode between materials with interest for tandem within a NW (GaInP/InP) has been demonstrated (see Figure c,d), but in the same article, the authors illustrate the difficulties associated with the doping value and profile of cathode and anode by trying different dopants and growth directions (p–n or n–p). Core–shell radial Esaki tunnel diodes have been reported as well. , …”
Section: Iii–v Nanowire Growth and Devicesmentioning
confidence: 99%
“…2019, 119, 9170−9220 h i b i t e d .value and profile of cathode and anode by trying different dopants and growth directions (p−n or n−p). Core−shell radial Esaki tunnel diodes have been reported as well 181,420.…”
mentioning
confidence: 99%
“…Compared to the p–n junction nanowires along the axis, core–shell p–n junction nanowires have more advantages in high-performance photodetectors. Because the junction area is larger in core–shell structure, the shell can passivate the core and reduce the defects and traps at the core surface. Also, due to the small diameter and thickness of the core and shell, most volume or even the whole nanowires are within the junction so that photogenerated carriers can separate and transport very effectively. However, growing III–V core–shell p–n junction nanowires is more difficult than growing p–n junction along the axis, and there is still no study on photodetectors based on p–n junction core–shell structure, to the best of our knowledge. ,,, Although electronic devices have been reported based on III–V core–shell nanowires, , only GaAs/AlGaAs and InAs/AlSb core–shell nanowires have been studied as photodetectors. ,, Note that these two materials are not p–n junction-type core–shell nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…a planar Si cell. The principle of a nanowire tandem cell has been first demonstrated by Heurlin et al 198 200 , while a radial tunnel junctions has recently been demonstrated by Tizno et al 201 . Although a multi-junction nanowire solar cell has not yet been realized experimentally, we like to emphasize that semiconductors with different lattice constant can be stacked into a single nanowire.…”
Section: Economics Of Nanowire Solar Cellsmentioning
confidence: 99%